Studies of genetic variability, heritability and genetic advance for yield component traits in bread wheat (Triticum aestivum L.) - Chethan Swamy Emmadishetty* and Deshraj Gurjar (Electronic Journal of Plant Breeding, 2022)
Thirty advanced lines of wheat obtained from Borlaug Institute for South Asia (BISA), Ludhiana, Punjab were evaluated in a Randomized Block Design (RBD) with three replications for yield and its contributing characters at Agriculture Research Farm, Department of Genetics and Plant Breeding, School of Agriculture, Lovely Professional University, Phagwara, Punjab, India during rabi 2021-2022. Genetic variability, heritability and genetic advance per cent of the meanand analysis of variance were carried out for 14 traits. The mean sum of square (MSS) due to genotypes was highly significant for all the fourteen traits. Grain yield per plant exhibited the highest phenotypic coefficient of variation (PCV) followed by harvest index, the number of spikes per plant, the number of tillers per plant and biological yield per plant. Genotypic coefficient of variation (GCV) was found to be highest for grain yield per plant followed by harvest index, the number of spikes per plant, the number of tillers per plant and biological yield per plant. Very high heritability estimates were associated with high estimates of genetic advance for the number of tillers per plant, the number of spikes per plant, biological yield per plant, harvest index, grain yield per plant, chlorophyll content, and flag leaf area which revealed the presence of additive gene effects, showing the efficiency of selection method of breeding for improving these attributes in wheat.